Adaptation to climate change in irrigated agriculture in Uzbekistan* - Shukhrat Mukhamedjanov; Azamat Mukhomedjanov; Rustam Sagdullaev; Nazokat Khasanova (Irrigation and Drainage, 2021)
In recent years, climate change in Central Asia, especially in Uzbekistan, has resulted in sharp alternation of dry and wet years. In such conditions, agriculture has turned into the most vulnerable sector. Agricultural producers have not been able to adapt to such variations of climatic conditions. Traditional irrigation approaches and agronomic operations are becoming unacceptable against the background of severe droughts or heavy rains. Moreover, intra‐annual distribution of precipitation and air temperature has changed. Especially in agriculture, increased rainfall in spring and summer and decreased rainfall in autumn and winter has had a negative impact. In 2013, the Global Water Partnership initiated the Water, Climate, and Development Programme for Caucasus and Central Asia. In the Fergana Valley of Uzbekistan, a project was implemented to study the possibility of agriculture adaptation to climate change within the framework of this programme. This article presents an analysis of long‐term data received from 1960 to 2014 on air temperature and precipitation. As a result of these studies, it has been determined that we can forecast the current year's weather conditions if we find a similar year in recent years. For the Fergana Valley of Uzbekistan, it has been established that we have a stable spring, when winter is cold with heavy precipitation, and we have a cold spring and summer with high precipitation, when we have a warm winter with low precipitation. Past experience has shown that the use of water for irrigation, taking into account climatic conditions, has a significant impact on reducing irrigation water and increasing crop yields.